An Enhanced IS-LM Business Cycle Model for Increasing Income in a Dynamic Economy - Diana, Arista Fitri; Rahmasari, Shafira Meiria; Mahardika, Dhimas (Universitas Muhammadiyah Semarang Press, 2023)
This paper introduces an enhanced IS-LM business cycle model by integrating control parameters using the Pontiyagin Maximum Principle Method, aiming to maximize income within economic cycles. It develops a dynamic model incorporating import and consumption rates as controls, showcasing their impact on economic variables through simulations and analytical methodologies. The results exhibit a significant increase in income by up to 10% through the reduction of interest rates and capital stock. The efficiency of the proposed controls is visually demonstrated, providing a robust validation of the methodology used, aligning with prior research, and offering substantial insights into dynamic business cycle modelling for economic analysis and policy-making.